Interactive HIV-1 Tat and Morphine-Induced Synaptodendritic Injury Is Triggered through Focal Disruptions in Na(+) Influx, Mitochondrial Instability, and Ca(2+) Overload - Fitting, Sylvia (Society for Neuroscience, 2014)
Synaptodendritic injury is thought to underlie HIV-associated neurocognitive disorders and contributes to exaggerated inflammation and cognitive impairment seen in opioid abusers with HIV-1. To examine events triggering combined transactivator of transcription (Tat)- and morphine-induced synaptodendritic injury systematically, striatal neuron imaging studies were conducted in vitro. These studies demonstrated nearly identical pathologic increases in dendritic varicosities as seen in Tat transgenic mice in vivo. Tat caused significant focal increases in intracellular sodium ([Na(+)](i)) and calcium ([Ca(2+)](i)) in dendrites that were accompanied by the emergence of dendritic varicosities. These effects were largely, but not entirely, attenuated by the NMDA and AMPA receptor antagonists MK-801 and CNQX, respectively. Concurrent morphine treatment accelerated Tat-induced focal varicosities, which were accompanied by localized increases in [Ca(2+)](i) and exaggerated instability in mitochondrial inner membrane potential. Importantly, morphine's effects were prevented by the μ-opioid receptor antagonist CTAP and were not observed in neurons cultured from μ-opioid receptor knock-out mice. Combined Tat- and morphine-induced initial losses in ion homeostasis and increases in [Ca(2+)](i) were attenuated by the ryanodine receptor inhibitor ryanodine, as well as pyruvate. In summary, Tat induced increases in [Na(+)](i), mitochondrial instability, excessive Ca(2+) influx through glutamatergic receptors, and swelling along dendrites. Morphine, acting via μ-opioid receptors, exacerbates these excitotoxic Tat effects at the same subcellular locations by mobilizing additional [Ca(2+)](i) and by further disrupting [Ca(2+)](i) homeostasis. We hypothesize that the spatiotemporal relationship of μ-opioid and aberrant AMPA/NMDA glutamate receptor signaling is critical in defining the location and degree to which opiates exacerbate the synaptodendritic injury commonly observed in neuroAIDS.